2008
DOI: 10.1128/jvi.02446-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adaptive Amplification of Preexisting Variation in an RNA Virus

Abstract: The amount and nature of preexisting variation in a population of RNA viruses is an important determinant of the virus's ability to adapt rapidly to a changed environment. However, direct quantification of this preexisting variation may be cumbersome, because potentially beneficial alleles are typically rare, and isolation of a large number of subclones is required. Here, we propose a simpler method. We infer the initial population structure of vesicular stomatitis virus (VSV) by fitting a mathematical model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The initial period of adaptation to an environment is the result of selection of preexisting variation [Dutta et al, 2008]. At early time points, fitness changes may be substantial without changes in the consensus sequence because a new beneficial allele on its way to fixation is at a frequency that is high enough to have a measurable effect of the population average, but still too low for detection as the dominant nucleotide in that position.…”
Section: Determinants Of Survival and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial period of adaptation to an environment is the result of selection of preexisting variation [Dutta et al, 2008]. At early time points, fitness changes may be substantial without changes in the consensus sequence because a new beneficial allele on its way to fixation is at a frequency that is high enough to have a measurable effect of the population average, but still too low for detection as the dominant nucleotide in that position.…”
Section: Determinants Of Survival and Adaptationmentioning
confidence: 99%
“…For example, host specificity of phage ⌽ -6 depends largely on receptor recognition, and the virus seems unable to produce a protein that can recognize multiple bacterial receptors simultaneously, so adaptation to new hosts usually results in loss of recognition of the old host receptor [Ferris et al, 2007]. Some environmental conditions may have an effect on the selection of specialists or generalists, such as interspecies competition [Johnson et al, 2009], coevolution with the host [Hall et al, 2011], or the supply of beneficial variation [Jasmin and Kassen, 2007], which does not seem to be limiting in RNA viruses [Betancourt, 2009;Bollback and Huelsenbeck, 2007;Dutta et al, 2008]. While there are some arguments as to whether true generalists exist in nature [Loxdale et al, 2011], arboviruses are usually considered the ultimate generalists due to their potential to replicate and perform well in a wide variety of hosts [Weaver, 2006].…”
Section: Selection For Generalization and Specializationmentioning
confidence: 99%
“…We have previously shown that the fitness change during the first 20 passages was domi-nated by the sampling of preexisting variation (4). Therefore, the fitness increases we observed were conceivably due to beneficial mutations carried over from the previous passages.…”
mentioning
confidence: 71%
“…Very severe bottlenecks turn on Muller's ratchet, a process that results in an increase in the genomic load of deleterious mutations, with a concomitant decline in fitness [12][13][14] that theoretically may drive populations to extinction [15]. Indeed, it has been shown for Vesicular stomatitis virus that the size of the bottleneck leading to the onset of Muller's ratchet depends on the fitness of the genotype used in the experiments and on the standing beneficial genetic variation present in the inoculum [16][17][18]. In large enough populations, such variation quickly amplifies and wipes out deleterious variants, thus slowing down and even reverting the fitness decay process.…”
Section: Introduction -An Essential Question In Evolutionarymentioning
confidence: 99%
“…So far, most of the studies mentioned exploring the interplay between N e , U b and v have been performed in oversimplified experimental systems such as cell cultures [1,2,[12][13][14][15][16][17][18] or in vitro with artificial media [3][4][5][6]. With this study, we want to expand this observations to a biologically fully realistic experimental system: the pathosystems formed by Tobacco etch virus (TEV; genus Potyvirus, family Potyviridae) and its natural host tobacco (Nicotiana tabacum L) and novel host pepper (Capsicum annuum L).…”
Section: Introduction -An Essential Question In Evolutionarymentioning
confidence: 99%